(untitled) (CIPEEX, 2025)
Introduction: This study reports the experience of a physiotherapy student at the Universidade Evangélica de Goiás – Campus Ceres, during an extracurricular supervised internship at the Basic Health Unit of Pilar de Goiás. Held from October 20 to November 20, 2024, the internship offered the opportunity to apply and improve assessment and intervention techniques in a real primary care setting. The experience provided significant learning about clinical practice and the importance of personalizing treatment, contributing to the professional development of the academy. Objective: The study aims to relate the experience of a physiotherapy student in an extracurricular supervised internship in physiotherapy at the Unit Basic Health in Pilar de Goiás. Methodology: This is an experience report based on the experience of a physiotherapy student from the Evangelical University of Goiás - Campus Ceres, in an extracurricular internship in physiotherapy at the Basic Health Unit of Pilar de Goiás, from October 20, 2024 to November 20, 2024, under the supervision of the physiotherapist responsible for the sector. Results: During her internship at the Basic Health Unit of Pilar de Goiás, from October 20th to November 20th, 2024, the physiotherapy student at the Universidade Evangélica de Goiás participated in 80 consultations for a total of 4 hours a day. Under supervision, he improved assessment and intervention techniques, obtaining a comprehensive view of clinical practice in primary care. The experience was crucial for developing their professional skills and understanding the personalization of treatment. Conclusion: The internship at the Basic Health Unit of Pilar de Goiás was crucial for the professional development of the physiotherapy student, offering valuable practical experience in primary care. With 80 supervised sessions, the student applied theoretical knowledge, improved her technical and clinical skills, and understood the importance of personalizing treatment. The experience solidified her commitment to ethical, patient-centered practice, preparing her for future challenges in physical therapy.